MicroRNA-185 regulates transforming growth factor-β1 and collagen-1 in hypertrophic scar fibroblasts - Xiao, Kaiyan (Mol Med Rep, 2017)
Transforming growth factor-β1 (TGF-β1) and collagen type I (Col-1) serve a critical role in the development and progression of hypertrophic scarring (HS). The present study hypothesized that a post-translational mechanism of microRNAs (miR) regulated the expression of TGF-β1 and Col-1 in HS fibroblasts (HSFBs). A collection of 20 HS tissues was compared with corresponding normal tissues from clinical patients, and the expression of miR-185 was measured. Using PicTar, TargetScan and miRBase databases, it was identified that miR-185 may be a regulator of TGF-β1 and Col-1 in humans. Based on these hypotheses, the expression of miR-185, TGF-β1 and Col-1 in HS tissues was investigated. The results demonstrated that the expression of miR-185 was markedly suppressed, and TGF-β1 and Col-1 levels were increased, in HS tissues. The expression levels of endogenous miR-185 negatively correlated with the TGF-β1 and Col-1 mRNA levels (Pearson's correlation coefficient r=−0.674, P<0.01 and r=−0.590, P<0.01, respectively). In vitro, miR-185 can regulate TGF-β1 and Col-1 through the predicted binding sites in its 3′-untranslated region. miR-185 had an effect on cell proliferation and apoptosis, thereby regulating HSFBs growth. In addition, miR-185 gain-of-function decreased TGF-β1 and Col-1 protein expression, and miR-185 loss-of-function increased TGF-β1 and Col-1 protein expression in HSFBs. In conclusion, overexpressed miR-185 could inhibit HSFBs growth, and the underlying mechanism was mediated, at least partly, through the suppression of TGF-β1 and Col-1 expression. However, above all, miR-185 might serve as a potential therapeutic approach for the treatment of HS.